If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4y + -7x + -7y = 0 Reorder the terms: 3x + -7x + 4y + -7y = 0 Combine like terms: 3x + -7x = -4x -4x + 4y + -7y = 0 Combine like terms: 4y + -7y = -3y -4x + -3y = 0 Solving -4x + -3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. -4x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 -4x + 0 = 0 + 3y -4x = 0 + 3y Remove the zero: -4x = 3y Divide each side by '-4'. x = -0.75y Simplifying x = -0.75y
| 3m+(m+1)=6m+1 | | 3e(3e-10)=2 | | 9x(x+2y+3z)= | | 6s^3+23s^2+33s=13s | | 3x-5=5+3x | | y+x^2-2x=0 | | x+y^2-2y=0 | | 10y+5x=100 | | 4y-24-9y+31= | | -4(y-3)=6y-38 | | f(-2)=-2+2(-2-1) | | -9x+-18+25=-38 | | 3+(-22)= | | 7-11x=x-33 | | 3log(7)(4)-5log(7)(m)= | | f(3)=3+2(3-1) | | -2x-10=44+8x | | 5t-2t=t | | 2z^2+7x=0 | | -4(2-y)+3y=4(y-4) | | (2x+4)(x-3)=0 | | f(-2)=-3(4-2)+2 | | 2x-3=4y+6 | | 4x^2-6x+5=x+1 | | 210x+100-72x^2=0 | | -9+4-(-5)= | | 8-3a^3=0 | | f(3)=-3(4-3)+2 | | X-6+2x=48 | | 64=-3(1-2n) | | 2x^2+28x+74=0 | | -65=136 |